Pendampingan Penyusunan Kelayakan Penbangunan Pabrik Es Mini pada Koperasi Kelompok Nelayan di Selatan Sukabumi - Edi Djatmika; Hermawan Hermawan; Adriana Sari Aryani; Kotim Subandi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Post-harvest handling of fish requires an effective cold chain system, including the availability of ice factories, to preserve the quality and freshness of catches. The presence of an ice factory enables fishermen to bring ice during fishing trips, ensuring the catch remains safe for consumption. The planning of a portable mini ice factory in Ciwaru Village, located within the Ciletuh National Geopark, aims to maintain fish quality along the southern coast of West Java. Although several ice factories exist in Sukabumi Regency, their availability at fish landing sites such as the Ciwaru Fish Auction Place (TPI) remains insufficient. According to the Regulation of the Minister of Marine Affairs and Fisheries No. 2 of 2021, assistance for ice factory construction is provided to fishermen groups following a feasibility study submission. This community service project aims to assist fishermen cooperatives in improving cold chain management and preparing a feasibility study for ice factory development. Key issues identified include limited human resource competence, hygiene and sanitation challenges, feasibility study preparation, and internal communication enhancement within cooperatives. Solutions are implemented through training programs, cold chain method applications, feasibility analysis for mini ice factories, and the development of an information system for fishermen. The planned ice factory unit has a capacity of 1 ton per 8-hour cycle, supported by three freshwater wells near the site. Economic analysis reveals an NPV of Rp1,170,676,141, an IRR of 10.91%, and a Net B/C Ratio of 1.64, with a BEP at 311 tons/year, well below the installed capacity of 788 tons/year, confirming its economic viability. The resulting feasibility study will serve as the basis for applying for government assistance, complemented by scientific publications, national media coverage, video documentation, and intellectual property registration.